2000
DOI: 10.1128/aem.66.9.3981-3986.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Vibrio parahaemolyticus O3:K6 from Asia

Abstract: A variety of serovars of the food-borne pathogen Vibrio parahaemolyticus normally cause infection. Since 1996, the O3:K6 strains of this pathogen have caused pandemics in many Asian countries, including Taiwan. For a better understanding of these pandemic strains, the recently isolated clinical O3:K6 strains from India, Japan, Korea, and Taiwan were examined in terms of pulsed-field gel electrophoresis (PFGE) typing and other biological characteristics. After PFGE and cluster analysis, all the O3:K6 strains we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
135
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 22 publications
6
135
1
2
Order By: Relevance
“…The clonal nature of the pandemic V. parahaemolyticus isolates was ascertained by the similarity of patterns obtained by genome restriction fragment length polymorphism-pulsed-fi eld gel electrophoresis (15), arbitrarily primed PCR (7,9), direct genome restriction enzyme analysis (DGREA) (4), and multilocus sequence typing (MLST) (16,17). However, the pandemic strain is a minor fraction of a diverse and shifting V. parahaemolyticus population found in shellfi sh in Puerto Montt (2).…”
mentioning
confidence: 99%
“…The clonal nature of the pandemic V. parahaemolyticus isolates was ascertained by the similarity of patterns obtained by genome restriction fragment length polymorphism-pulsed-fi eld gel electrophoresis (15), arbitrarily primed PCR (7,9), direct genome restriction enzyme analysis (DGREA) (4), and multilocus sequence typing (MLST) (16,17). However, the pandemic strain is a minor fraction of a diverse and shifting V. parahaemolyticus population found in shellfi sh in Puerto Montt (2).…”
mentioning
confidence: 99%
“…Otros serotipos como O4:K68, O1: KNT (no tipificable), O1:K25, O1:K41, O4:K12, han emergido en diversas regiones del mundo, determinán-dose por variados estudios moleculares su asociación genética con el clon pandémico O3:K6 37,38,9 .…”
Section: Aspectos Microbiológicosunclassified
“…Vibrios of seafood origin have attracted increasing attention from time to time as it is found to be one of the most important causes of human food poisoning. Earlier reports revealed food poisoning due to the consumption of seafood contaminated with Vibrio species, particularly Vibrio parahaemolyticus (Wong et al 2000). The incidence of this bacterium increased considerably during recent years in US, Japan and Korea (Lee et al 2001), and in India it was reported to be doubled in the last 5 years (Chowdhury et al 2000).…”
Section: Introductionmentioning
confidence: 99%